Evaluasi Kesesuian Subjek Skripsi dengan Roadmap Penelitian di Fakultas Kehutanan Universitas Lancang Kuning Tahun 2017-2021 - Barus, Leady Yurmeli Br (CV. ITTC INDONESIA, 2023)
This research is a type of descriptive research. The population in this study is all 2017-2021 theses, namely 131 theses. This study used a purposive sampling technique. The method used to collect data for the 2017-2021 Faculty of Forestry Thesis was to conduct observations and interviews with the Study Program section of the Faculty of Forestry, Lancang Kuning University. Based on the results of the research above, it can be concluded that the number of theses, namely the thesis of the 2017 Faculty of Forestry students, has done a lot of research on the subject of the economics of forest resources. The 2018 Faculty of Forestry Student Thesis has the most research on the subject of ecotourism and environmental services. In 2019 the thesis is dominated by the subject of conservation. The Student Thesis of the Faculty of Forestry in 2020 has a total of subjects that have been extensively researched on natural resource and environmental conservation. In 2021 thesis is dominated by the subject of silvilculture, forest entrepreneurship, ecotourism and environmental services.